الاختلاطات التوليدية في الحمل التوأَمي )خبرة مشفى الأَسد الجامعي باللاذقية( - النقري, محمد; مرعي, رئيفة; الجاسر, حافظ (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة الاختلاطات التوليدية للحمول التوأَمية في مشفى الأسد الجامعي في اللاذقية من (1/1/2004) وحتى (1/6/2006 )، وكان عدد الحالات /105/ حالة ولادة مع عينة مقارنة من الحمول المفردة، وبعد متابعة سير المخاض والولادة تم تحديد الاختلاطات التي عرقلت سيره وكانت النتائج كالآتي: 1- ارتفاع نسبة الولادة المبكّرة (54.4%) المجيئات المعيبة (43.8%) ونزوف الخلاص (13.1%) وانسدال السرر (10.5%) وعسرة المخاض بنقص المقوية (7.6%) مقارنة مع الحمل المفرد. 2- ارتفاع نسبة القيصريات في الحمول التوأمية (46.7%) مقارنة مع الحمل المفرد. 3- ارتفاع نسبة المجيئات المعيبة وانسدال السرر وانفكاك المشيمة في ولادة التوأم الثاني نسبةً للأول. الخلاصة: ازدياد معدل الاختلاطات الوالدية في سير مخاض الحمول التوأمية نسبة للحمول المفردة، مما يتطلب الحذر والمراقبة الجادة للمخاض والولادة. Our study dealt with the obstetrical complications in twin pregnancies at Al-Assad University Hospital from 1/1/2004 to 1/6/2006; it included /105/ cases with twin pregnancies and /105/ cases with single pregnancies. after monitoring labor in both groups and specifying the complications concerned, the results were as follows: 1- An increase in premature birth (54.4%), malpresentation (43.8%), post partum haemollhage (13.1%), cord prolepses (10.5%), and atonic contraction (7.6%) compared with single pregnancies. 2- An increase in caesarian sections in twin pregnancies (46.7%) compared with single pregnancies. 3- An increase in malpresentation, cord prolepses, and placenta abruption in the second fetus compared to the first. The rate of maternal complications increased during labor for twin pregnancies, and that made us take extra care when observing and delivering.